Durability of Na2O-RO-SiO2 glasses in water - Pyare R.; Srivastava M.R.C.; Nath P. (My University, 2025)
The effect of divalent cation ions on chemical durability was studied in the base glasses 16Na2O-1ORO-74SiO2. In order to keep the same surface area, a fixed volume of glass powder was exposed to the corroding action of water. The amount of SiO2 and alkali extracted was determined. The chemical durability of glass was found to increase with increasing bond strength between the divalent cation and the non-bridging oxygen ion. © 1982 Chapman and Hall Ltd.